Synthesis Design of Dual-Band Filtering Power Dividers Based on E-Shape Resonators - Shen, Jiwei; Li, Wei; Ping, Kang; Zhang, Zhuowei; Shu, Minghan (Frontiers in Physics, 2022)
In this study, a comprehensive design of dual-band filtering power dividers (FPDs) with arbitrary phase distribution is presented. With a series of analytical equations for the direct synthesis design, the proposed method shows its great capacity of designing dual-band FPDs with any pre-specified responses, arbitrary phase distribution, and high isolation. To verify this design method, a demonstrated dual-band FPD with 90° phase differences between two outputs based on E-shape resonators has been implemented. The emulational results coincide with the measured results well, showing the feasibility of the proposed method.